SIVRAD: an integrated system for the assessment of the environmental risk from solid waste landfills - Guidelines - Rapti, Dimitra; Masi, Salvatore; Sdao, Francesco (Acque Sotterranee - Italian Journal of Groundwater, 2021)
In recent years, the contamination of the underground resources from landfill leachates is recognised as a serious socio-economic and environmental problem in many countries. In fact, the existing not adequately controlled and abandoned sites, constitute a serious sanitary and environmental problems. The choice of the waste disposal site must necessarily arise from a rigorous study based on the joint assessment of the environmental hazard of the same plant and the hydrogeological characteristics and the degree of intrinsic vulnerability to pollution of the aquifers. In the present paper an integrated system for the assessment of the environmental risk from solid waste landfills is proposed. The integrated analysis of the intrinsic vulnerability of the aquifer system and the estimate of the intrinsic potential hazard caused by the landfill expressed in terms of danger index allow to evaluate the suitability of the sites to host a landfill and to define the reclamation priority and monitoring system for the existing landfills. As concerns new landfills, the proposed methodology could also support a better construction strategy and the protection of the surrounding environment. Finally, this methodological approach was applied in landfills located in different geological and hydrogeological contexts.